2019
DOI: 10.1017/aap.2018.45
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Photogrammetry in Three Bioarchaeological Contexts: Steps for In-Field Documentation

Abstract: Human skeletal remains hold a wealth of information about past life-ways, but their documentation and recovery from archaeological contexts is challenging. Four challenges face bioarchaeological field work: poor skeletal preservation; complex mortuary traditions; sub-par excavation conditions; and excavation time limits. Poor preservation often prevents the collection of metric data from skeletons. This project tested whether a bioarchaeologist with basic photography skills and excavation equipment could addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Archaeological projects focusing on digitizing artifacts are now ubiquitous, based on the need to document features prior to and during excavation (see Novotny, 2019), preserve archaeological resources, and carry out the mission of public museums to increase access. The millions of cultural items suddenly lost in the burning of the National Museum of Brazil puts this necessity in perspective, and efforts are now underway to create a digital record of some of these by crowdsourcing photographs by the public of the objects that were on display to build 3-D models (Killgrove 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Archaeological projects focusing on digitizing artifacts are now ubiquitous, based on the need to document features prior to and during excavation (see Novotny, 2019), preserve archaeological resources, and carry out the mission of public museums to increase access. The millions of cultural items suddenly lost in the burning of the National Museum of Brazil puts this necessity in perspective, and efforts are now underway to create a digital record of some of these by crowdsourcing photographs by the public of the objects that were on display to build 3-D models (Killgrove 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this method was determined to be a more expedient method compared to hand-drawn maps of individual burials, thereby saving on time and financial resources. Other scholars have also found that 3D documentation methods are time efficient and more accurate (Douglass et al 2015; Koenig et al 2017; Novotny 2019; Olson et al 2013; Sapirstein and Murray 2017).…”
Section: Sfm Photogrammetry Of Burials: Design and Objectivesmentioning
confidence: 98%
“…The use of structure from motion (SfM) photogrammetric techniques for documentation in archaeological work has boomed in the last few years, and it is on track to becoming integrated into the standard tool set of the archaeologist of the twenty-first century (De Reu et al 2013, 2014; Koenig et al 2017; Matthew et al 2014; Novotny 2019; Sapirstein and Murray 2017; Ulguim 2017). Although photographs and hand-drawn maps on graph paper have been—and still are—the conventional method of documentation, digital 3D models threaten to dethrone the photograph as the industry's future standard for visual and metric data collection (De Reu et al 2014; Morgan et al 2019; Sapirstein and Murray 2017).…”
mentioning
confidence: 99%
“…The decade of work, collegiality, and friendship between the author and CRIA staff has ensured that the collection is well protected, and similar methods are being applied to other at-risk materials within the CRIA and region. Finally, one must also consider how new technology such as photogrammetry (see Novotny 2019 and Wrobel et al 2019, in this issue), photo documentation of box contents (Cassman and Odegaard 2007), and digital inventories (e.g., McManamon and Kintigh 2010) can protect previous data and reduce the need to handle delicate materials in extant collections.…”
Section: Recommendations For the Field And Laboratorymentioning
confidence: 99%